Pemberdayaan Pengrajin Kerupuk UD Mekar Jaya Desa Selimau 3 Bulungan melalui Peningkatan Kapasitas Produksi dan Manajemen Usaha: Pengabdian - Pangerang, Fitrah; Rusyanti, Nila; Wahyudi, Eko (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Community Partnership Program (PKM) for UD. Kerupuk Mekar JayaThis Community Partnership Program (Program Kemitraan Masyarakat/PKM) aims to increase production capacity and strengthen marketing management for the micro, small, and medium enterprise (MSME) UD. Kerupuk Mekar Jaya in Selimau 3 Village, Tanjung Selor, Bulungan Regency. The activities focus on two aspects: the application of appropriate technology in the form of designing and building a semi-automatic, electric-motor-powered cracker slicing machine, and a soft innovation product consisting of digital marketing and business management training.Before the intervention, the cracker production process was manual, yielding a capacity of approximately 30 kg per day, involving 8-10 workers, and requiring an effective working time of 8-12 hours. Following the implementation of the semi-automatic slicing machine, a significant increase in production capacity occurred, reaching 100 kg per day, with labor efficiency reducing the workforce to 3-4 people and production time decreasing to 3-4 hours per day. This increase reflects a productivity gain of more than 230% and a working time efficiency of 60-70%. Furthermore, the management and digital literacy training successfully enhanced the partner's ability to market products through online platforms such as social media. Overall, the program had a tangible impact on the sustainability of the small business and strengthened the MSME's position as the cracker production center in the region.